Literature Review Analysis Of Application Of Electronic Medical Records In Hospitals - Andi Karisma Nurdiyansyah; Ades Dwi Natalia; Imaniar Sevtiyani (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: This research on electronic medical records referring to Human Organization Technology (HOT-fit) procedure aims to figure out factors that affect implementation of electronic medical records that are in line with the cases investigated in this research.Objective: Knowing the implementation of electronic medical records in hospitals with the HOT-Fit method from various journals.Methods: Literature review to examine five journals on electronic medical records in hospitals with the HOT-fit method. Secondary data are collected and analyzed descriptively.Results: Based on 6 journals analyzed, it is shown that the implementation of EMR can facilitate staff in medical services. Human factor in system usage variables is an important part and has the biggest benefits. System implementation also becomes a main requirement in EMR operations that can be measured from system’s benefits such as on performance, efficiency and effectiveness on an organization activity.Conclusion: Human Factor plays the major influence, but it has to be monitored. Technological factors. Organization factor shows that RME is already adjusted with user needs and ease of use